The morphological structure in the macrophages of leprosy pigment - Taha, Jarjees (Humanities Journal of University of Zakho, 2018)
This research is entitled "The Conditional Structure in the Poems of the Son of Pigment Leprosy", a study of the structure and significance, and the son of the pigmentist leprosy of the poets who gathered the illustrious to the art of poetry; he was the poets of the shawls in Andalusia, a poet of the seventh century AH, Andalus. I have been led to this research a lot of literary and monetary studies on the art of Almushahat, and the scarcity of linguistic studies in general, and grammatical studies in particular, and the choice of son of pigment; was a feature characterized by Moshaha is almost exclusively the purpose of praise and nostalgia to visit the tomb of the Prophet peace be upon him With the fluency of the language and its ease compared to other candidates. It was characterized by these specimens of Ibn al-Sabbagh the multitude of structural phenomena in the condition of the condition, which is frequently repeated between the sides of the descriptive texts, was that the study of these phenomena after the presentation of the structural patterns on which the conditional structure. And the extension of the construction in the conditional structure in the condition and in the answer to both, and detailing the means of this prolongation syntactically and showing their effect, as well as the study of another feature in Moshat Ibn al-Sabbagh, which is deleted Answer condition. The search for the phenomena in which Ibn al-Sabbagh approved the syntactic phenomena in the grammarians and then revealed the phenomena in which the grammatical rule was violated in the section of the condition, such as deleting the answer from its place. The research concluded by presenting the results of the analytical description of the condition in its specifications and proved the sources and references adopted in the research.